2006
DOI: 10.1016/j.jad.2006.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the assessment of bipolar spectrum disorders in the WHO CIDI 3.0

Abstract: Objective-Although growing interest exists in the bipolar spectrum, fully structured diagnostic interviews might not accurately assess bipolar spectrum disorders. A validity study was carried out for diagnoses of threshold and sub-threshold bipolar disorders (BPD) based on the WHO Composite International Diagnostic Interview (CIDI) in the National Comorbidity Survey Replication (NCS-R). CIDI BPD screening scales were also evaluated.Method-The NCS-R is a nationally representative US household population survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 43 publications
1
131
1
2
Order By: Relevance
“…1 Family, twin and adoption studies have established a substantial genetic contribution, with heritability estimates averaging about 70%. 2 The high heritability has provided a strong rationale for molecular genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…1 Family, twin and adoption studies have established a substantial genetic contribution, with heritability estimates averaging about 70%. 2 The high heritability has provided a strong rationale for molecular genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision (DSM-IV-TR), the lifetime community prevalence of bipolar II disorder is 0.5%, but recent studies have reported lifetime prevalence rates of around 1.5-2%. [1][2][3][4] The course of the illness is characterized by recurrent episodes of hypomania and depression interspersed with periods of euthymia. Patients are symptomatic for >50% of the time, with depression of varying severity being the most common symptom.…”
mentioning
confidence: 99%
“…Mood disorders have diverse and sometimes paradoxical definitions. Hagop Akiskal defines bipolar disorders along a spectrum that comprises eight types (1)(2)(3)(4). The fifth edition of the "Diagnostic and Statistical Manual of Mental Disorders (DSM-5)" and the 10th revision of "The International Classification of Diseases (ICD 10)" provide somewhat different definitions of these disorders.…”
Section: Contextmentioning
confidence: 99%